- #1

rabbed

- 243

- 3

How do I use this formula:

ni = (e^(B*(eH-ei))-1)*e^(-0.5772156649..)

from this paper?

https://ui.adsabs.harvard.edu/abs/2018DDA...49P...2C/abstract

According to this site, (n0,n1,n2,n3,n4,n5,n6,n7) = (3,2,1,1,0,0,0,0) for N=7:

https://bouman.chem.georgetown.edu/S02/lect21/lect21.htm

Does that mean I should get:

n0 = (e^(B*(7-0))-1)*e^(-0.5772156649..) = 3

n1 = (e^(B*(7-1))-1)*e^(-0.5772156649..) = 2

n2 = (e^(B*(7-2))-1)*e^(-0.5772156649..) = 1

n3 = (e^(B*(7-3))-1)*e^(-0.5772156649..) = 1

?